Selfish and Prospective. Theory and Evidence of Pocketbook Voting - Mikael Elinder; Henrik Jordahl; Panu Poutvaara (Aboa Centre for Economics (ACE), 2008)
We present and test a theory of prospective and retrospective pocketbook voting. Focusing on two large reforms in Sweden, we establish a causal chain from policies to sizeable individual gains and losses and then to voting. The Social Democrats proposed budget cuts affecting parents with young children before the 1994 election, but made generous promises to the same group before the 1998 election. Since parents with older children were largely unaffected we use a difference-in-differences strategy for identification. We find clear evidence of prospective pocketbook voting. Voters respond to campaign promises but not to the later implementation of the reforms.
Keywords: C21; D72; H50; 330; elections; economic voting; pocketbook voting; selfinterest; prospective voting; retrospective voting; child care